Penyelesaian gelombang solitari : kaedah analisis Painleve Invarian dan sistem persamaan Riccati terlurus dengan pekali pembolehubah - Mohamad, Mohd. Nor (Department of Mathematics, Faculty of Science, 2005)
A new method to find solitary wave solutions of the nonlinear evolutions is investigated. The method of invariant PainlevÂ´e analysis and linearised Riccati system of equations with variable coefficients, abbreviated as APIRTP is a method based on singular manifold analysis. The expressions of the singular manifold are simplified in the form of Schwarzian derivative S. S is a variable coefficient of the Riccati equations. By using the APIRTP method, the truncated solution expansions and solitary wave solutions of the KdV and HKdV equations are obtained